Sexual behaviors in male sex workers in Spain: Modulating factors. (February 2014) - Ballester, Rafael; Salmerón, Pedro; Gil, María D; Giménez, Cristina
This study analyzed how the culture of origin, educational level, sexual orientation, and experience of male sex workers may mediate their commercial sexual behaviors. A total of 100 Spanish agency male sex workers were interviewed. Most of them were young men, Latin American, homosexual, and had middle-level education. Our results showed that cultural differences and sexual orientation could influence male sex workers when engaging in sexual behaviors with their clients. Social and health projects with male sex workers may have to take into account sexual myths and taboos related to sexual orientation and cultural differences.